ANALISIS HUKUM TERHADAP UTANG DEBITOR DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG: LEGAL ANALYSIS OF DEBT DEBTORS IN DEBT PAYMENT OBLIGATION DELAY - Irfan, Irfan; Tira, Andi; M. Jafar, Juliati (Clavia, 2022)
This study aims to determine the application of formal and material requirements in the application for Postponement of Debt Payment Obligations in Decision Number 1/Pdt.Sus-PKPU/2020/PN Niaga Mks and the implementation of protection of creditor interests in the application for Postponement of Debt Payment Obligations in Decision Number 1/Pdt. Sus-PKPU/2020/PN Niaga Mks. The type of research used is empirical juridical, with data collection techniques through library research methods and field research methods using interview research instruments. and documentation. The data of this study were analyzed descriptively qualitative. Based on the researcher's analysis that the application of the formal and material requirements in the decision Number 1/Pdt.Sus-PKPU/2020/PN Niaga Mks has fulfilled the provisions stipulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, the application for postponement of obligations debt payments can be granted. Since the stipulation of the postponement of debt payment obligations by the Panel of Judges. Creditors who as applicants for PKPU have fulfilled the protection of their interests, creditors get their rights and interests during the process of requesting a postponement of debt payment obligations, but creditors cannot directly collect debts from debtors because of the provisions and the judge has appointed a curator or implementation supervisory body in the process. request for postponement of debt payment obligations (PKPU). Based on the researcher's analysis that in the decision Number 1.Pdt.Sus-PKPU/2020/PN Niaga Mks the implementation of the creditor's interest in the ongoing application for the postponement of the obligation to pay debts has fulfilled the provisions, protection and interests of the creditor have been fulfilled